2021
DOI: 10.4269/ajtmh.20-1650
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Human Papillomavirus Vaccine Acceptability among Women in South India: An Exploratory Study

Abstract: Cervical cancer is the second leading cause of cancer and one of the leading causes of cancer-related death in women in India. Human papillomavirus (HPV) vaccine uptake in India is low due to cost, low awareness of HPV, social stigma, and other factors. We assessed the awareness, attitudes, and beliefs regarding HPV and HPV vaccination and explored the barriers and challenges to HPV vaccine intent among women in Mangalore, India. An exploratory study was conducted using two focus group discussions (FGDs) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Additionally, factors such as stigma associated with a vaccine that prevents sexually transmitted infections in adolescents have impacted acceptability and uptake of HPV vaccines across different regions ( Escoffery et al, 2019;16. PMID: , Lim and Lim, 2019 , Shah et al, 2021 ). As such, conscientious public health interventions are needed to promote HPV vaccination efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, factors such as stigma associated with a vaccine that prevents sexually transmitted infections in adolescents have impacted acceptability and uptake of HPV vaccines across different regions ( Escoffery et al, 2019;16. PMID: , Lim and Lim, 2019 , Shah et al, 2021 ). As such, conscientious public health interventions are needed to promote HPV vaccination efforts.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Specifically, the lower HPV vaccination rate in Asian Indian women may relate to family influence because Asian Indian parents are less likely to encourage their daughters to get the HPV vaccine owing to stigma against sexual activities. 24 , 25 In addition, previous research has shown that Asian Indians are not as engaged in preventive healthcare as OA subgroups. 26 Acculturation and generation status can also influence HPV vaccine uptakes because studies have shown that first-generation immigrants are less accepting of the HPV vaccine than second-generation immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…The world's most populous country of 1·39 billion, India has also been deemed the world's largest producer and distributor of COVID-19 vaccines ( Shah et al, 2021 ). According to the Union Health Ministry, India's COVID-19 vaccination experience triggered rapid development, popularisation, and large-scale administration of vaccines, i.e., above 90 % of eligible people with the first dose & 65 % with the second dose.…”
mentioning
confidence: 99%